Compulsory Education as a Fulfilment of Children’s Right to Education Based on the Principles of Non-Discrimination and the Best Interests of the Child - Iman, Candra Hayatul; Apriani, Rani; Marpaung , Devi Siti Hamzah; Arafat, Muhammad Rusli (Kosmik Hukum, 2025)
Education is essential for human development, enabling individuals to cultivate their potential through formal learning processes and other socially recognized means. It serves as a transformative tool that shapes human character and broadens knowledge. This study aims to analyze the implementation of policies related to the fulfillment of children's right to education within the compulsory education program in Dongkal Village, Pedes District, Karawang Regency. The research employs a normative juridical approach, examining the application of legal provisions in practice and their role in addressing legal issues within society. A qualitative research method with a prescriptive analysis approach is utilized to critically evaluate the effectiveness of these policies. This study not only assesses the fulfillment of children's educational rights but also contributes to a broader discourse on sustainable development by integrating legal and socio-economic perspectives. The findings of this research provide valuable insights into the effectiveness of compulsory education policies and their implementation at the local level. Furthermore, this study offers recommendations for policymakers to enhance the legal framework governing compulsory education, ensuring equitable access to quality education for all children. By addressing gaps in policy enforcement and aligning educational initiatives with human rights principles, this research contributes to the development of more inclusive and sustainable education policies in Indonesia.